Endurant stent graft demonstrates promising outcomes in challenging abdominal aortic aneurysm anatomy - Mwipatayi, Bibombe P.; Faraj, Joseph; Oshin, Olufemi; Fitridge, Robert; Wong, Jackie; Schermerhorn, Marc L.; Becquemin, Jean-Pierre; Böckler, Dittmar; Riambau, Vincente; Teijink, Joep AW.; van Sambeek, Marc R. H. M.; Verhagen, Hence (Journal of vascular surgery, 2021)
Objective - We aimed to assess the 5-year safety and effectiveness outcomes of patients enrolled in the Endurant Stent Graft Natural Selection Global Post Market Registry (ENGAGE) who were treated outside the approved indications for use (IFU) of the Endurant stent graft. - Methods - Our primary outcome measure was 12-month treatment success, defined as successful endograft delivery and deployment and the absence of type I or III endoleak, stent migration or limb occlusion, late conversion, and abdominal aortic aneurysm diameter increase or rupture. Secondary outcome measures included 30-day all-cause mortality, major adverse events, secondary procedures, technical observations, aneurysm-related mortality, and all-cause mortality within 12 months. - Results - Demographic characteristics of ENGAGE patients treated outside (225 [17.8%]) and within (1038 [82.2%]) the IFUs were similar, except that female patients comprised a much higher percentage of the outside IFU group (19.1% vs 8.7%; P < .001). The outside IFU group presented with lower rates of coronary artery disease and cardiac revascularization and a greater number of symptomatic patients compared with the within IFU group (21.3% vs 15.0%; P = .020). Technical success was achieved in more than 99% of all patients. The outside and within IFU groups showed a comparable and low occurrence of uncorrected type I (0.9% vs 1.2%; P = 1.00) and type III endoleak (0.4% vs 0.3%; P = .54) immediately after device implantation. The 5-year freedom from type IA endoleaks was 89.4% vs 96.7% (P < .0001) for those patients outside and within the IFUs, respectively, although both groups had similar type III endoleaks through 5 years (P = .61). Stent graft limb occlusion estimated overall survival, and freedom from aneurysm-related mortality and endovascular interventions were comparable in both patient groups through the 5-year follow-up. The Kaplan-Meier estimates at 5 years showed a trend for low but increased need for type I or III endoleak correction procedures in the outside IFU group compared with the within IFU group (7.2% vs 5.2%; P = .099). - Conclusions - Differences were not observed in all-cause mortality, aneurysm-related mortality, and secondary procedures between within and outside IFU patients through a 5-year follow-up in the ENGAGE registry. Proximal necks with angulation or diameters outside the IFUs were the most common reasons for patients identified as being outside IFU, and the cohort had increased incidence of type IA endoleaks. Despite the challenges presented from the broad range of aortic and abdominal aortic aneurysm morphologies, the Endurant stent graft showed promising 5-year outcomes.